Quality of Friendship on Identity Formation in Adolescents in Surabaya - Khristi, Theodora Carelina; Kurniawan, Afif (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Adolescence is a transition period from childhood to adulthood that has a developmental task to shape their identity. Adolescence is a time when individuals spend more time with friends, interact more with peers and do many activities together with peers. The purpose of this study is to look at the relationship between the quality of friendship and the dimension of identity formation in adolescents. This research is a quantitative survey with the criteria for teenage respondents domiciled in Surabaya aged 12-21 years (N=489) as well as the provisions that have been set by the research in accordance with the research objectives. Data was obtained using open questionnaires related to demographic data and closed questionnaires with friendship quality scale (Friendship Quality Scale) and identity dimension scale (Utrecht-Management of Identity Commitmens Scale). The contained data was analyzed using the Spearman Non Parametic relationship test. The results of the analysis showed that there was a significant relationship between the quality of friendship and the commitment dimension (r=0,496 and p=0.001) and the depth exploration dimension (r=0,427 and p=0.001) but there was no significant relationship with the commitment review dimension (r=-0,049 and p=0,275). Commitment is an indicator of an individual's success in achieving identity based on an in-depth exploration process with the role of the quality of friends in the process so that the identity achieved by the individual is in accordance with.Remaja merupakan masa transisi dari kanak-kanak menjadi dewasa yang memiliki tugas perkembangan untuk membentuk identitas dirinya. Masa remaja merupakan masa individu menghabiskan waktu lebih banyak bersama dengan teman-teman, lebih banyak berinteraksi dengan teman sebaya serta melakukan banyak aktivitas bersama dengan teman sebaya. Tujuan penelitian ini untuk melihat hubungan antara kualitas pertemanan dan dimensi pembentukan identitas pada remaja. Penelitian ini bersifat kuantitatif survei dengan kriteria responden remaja berdomisili di Surabaya berusia 12-21 tahun (N=489) serta ketentuan-ketentuan yang telah ditetapkan oleh penelitian yang sesuai dengan tujuan penelitian. Data diperoleh dengan menggunakan angket terbuka terkait dengan data demografis dan angket tertutup dengan skala kualitas pertemanan (Friendship Quality Scale) dan skala dimensi identitas (Utrecht-Management of Identity Commitmens Scale). Data yang tertampung dianalisis dengan menggunakan uji hubungan Non Parametik Spearman. Hasil analisis menunjukkan bahwa terdapat hubungan yang signifikan antara kualitas pertemanan dengan dimensi komitmen (r=0,496 dan p=0,001) dan dimensi eksplorasi mendalam (r=0,427 dan p=0,001) namun tidak terdapat hubungan yang signifikan dengan dimensi peninjauan kembali komitmen (r=-0,049 dan p=0,275). Komitmen merupakan indikator keberhasilan individu mencapai identitas berdasarkan proses eksplorasi mendalam dengan peran kualitas perteman dalam proses proses tersebut sehingga identitas yang dicapai oleh individu sesuai dengan dirinya.